2018
DOI: 10.1161/strokeaha.118.021517
|View full text |Cite
|
Sign up to set email alerts
|

Prior Intravenous Stroke Thrombolysis Does Not Increase Complications of Carotid Endarterectomy

Abstract: Background and Purpose- Carotid endarterectomy (CEA) is recommended within 14 days after carotid artery stroke to prevent recurrence. However, the optimal timing of CEA after intravenous thrombolysis (IVT) remains unclear. We studied the safety of CEA after IVT while taking into account both stroke recurrence and CEA-related complications. Methods- Patients who underwent IVT followed by CEA in Helsinki University Hospital 2005 to 2016 were withdrawn from prospectively collected registers. The incidence of stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
5
3
Order By: Relevance
“…Compared to the previous similar study that found a 5.5% risk of preoperative stroke in IVT-treated, 8 our risk was slightly more than double (12%). By our Kaplan-Meier approach, we took the variable timing to CEA/CAS into account, the previous study did not.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Compared to the previous similar study that found a 5.5% risk of preoperative stroke in IVT-treated, 8 our risk was slightly more than double (12%). By our Kaplan-Meier approach, we took the variable timing to CEA/CAS into account, the previous study did not.…”
Section: Discussioncontrasting
confidence: 94%
“…Indeed, an association between IVT and early clinical worsening was recently shown for all-cause carotid occlusion (including embolic occlusion) within 3 hours of baseline imaging. 7 To date, a single study has been presented and showed a 5.5% risk of preoperative stroke recurrence, 8 lower than the ≈ 15% risk seen in other studies. 2,3 However, this study had no control group without IVT treatment and possible selection bias as only cases that subsequently underwent carotid endarterectomy (CEA) were included.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Ijas et al found that early CEAs (within 48 hours from IV thrombolysis) did not differ from CEAs performed later regarding peri/postoperative strokes, neck hematomas, MI, or 3-month modified Rankin Scale. 14 Similarly, despite our emergency CAS group included patients with tandem occlusions during thrombectomy (24%) and had a significantly higher number of ipsilateral carotid occlusions (17% vs. 2%) and patients undergoing general anesthesia (19% vs. 4%), there were no differences in the primary and secondary outcomes with the elective CAS group. These findings provide additional evidence that early carotid revascularization (CAS or CEA) in high-risk groups such as thrombectomy patients might be safe.…”
Section: Discussionmentioning
confidence: 82%
“…29 In a series of operations after thrombolysis, seven of 128 (5.5%) patients had a recurrent stroke prior to surgery a median of four days (interquartile range 0e8 days) after the thrombolysis, whereas the 30 day peri-/post-operative stroke rate was six of 128 (4.7%). 30 This means that operating promptly remains important, despite improved medication.…”
Section: Delay and Sexmentioning
confidence: 99%